Counselling and Screening of Hepatitis B Virus Infection In Dukuh Kupang Community, Dukuh Pakis District, Surabaya. (January 2019) - Wungu, C D K; Khaerunnisa, S; Humairah, I; Lukitasari, L; Qurnianingsih, E; Prabowo, G I; Sudarno,; Handajani, R; Suhartati,
Abstract: Background . Indonesia is a country with high endemicity of Hepatitis B Virus (HBV) infection. HBV infection is still a problem in society due to limited knowledge of the community and lack of available access to its diagnosis and treatment. Patients with hepatitis B each year is steadily increasing, especially in areas with high risk, including former prostitution area in Surabaya such as in Dukuh Pakis District. Aims. This activity was aimed to give understanding of HBV infection and perform early detection of HBV infection in Dukuh Kupang Community, Dukuh Pakis District, Surabaya. Methods. A community service in the form of counselling to increase knowledge and understanding of hepatitis B was done to community in Dukuh Kupang, Dukuh Pakis Regency, Surabaya. Pretest and post test were conducted to determine the initial understanding and post socialization knowledge for these people. Laboratory tests such as HBsAg and ALT were performed for screening of HBV infection. Private counselling for participants who positively detected infected with HBV was also done. Results. Based on the summary of pretest and post test from the participants, an increase in participants' knowledge of hepatitis B was found. The number of participants followed laboratory examination were 58 participants from 72 participants who attended counselling. From the laboratory results, as much as 3 positive participants (5.17%) were newly found infected with HBV, proved with positive HBsAg. One participant of them has increased ALT. Further counselling and assistance for participants with positive HBsAg were performed. Conclusion. Counselling was effective to increase knowledge of hepatitis B for Dukuh Kupang Community. Screening also found naive HBV infection in these people. Similar program can be performed in communities in other areas to increase prevention and early detection of HBV infection in Indonesia, especially Surabaya.